Islamism and Islamic-Turkish Unityin the Worldview of Hashim bey Vazirov - Alakbarli, Faig (Scholarya Demo Journal of Ruby, 2023)
The article examines Islamism, Islamic unity, Islamic-Turkish unity, Eurocentrism, modernization, and other issues that occupy an important place in the worldview of Azerbaijani thinker Hashim Bey Vazirov. In Vazirov's standpoint, the new essence of Islam, the importance of Islamic unity, and its adaptation to the conditions of the modern era are of great importance. The thinker regarded enlightenment as a crucial tool for the national awakening of the Azerbaijani people and advocated for religious reforms in society. H.B. Vazirov, while criticizing the Muslim world, which has been in decline for the past centuries, avoided radicalism and strived to approach these issues carefully.The main target of Vazirov's criticism was not Islam itself, but rather hypocritical clergymen speaking on behalf of that religion. The thinker focused on reforming and uniting Muslims to adapt to the requirements of the modern era. His thoughts on the Islamic religion show that, as a public figure, he was confident and hopeful about the awakening of the Muslim world and its transition from darkness to light. From this point of view, Vazirov's thoughts about Islam and Islamism remain extremely relevant even in contemporary times.It is mentioned in the article that Vazirov in time observed that Islam and Turkism, especially Islam, were subjected to criticism by many people in the Western world, and he tried to provide appropriate explanations. In any case, the attitude of the Western world towards Islam and Turkism, approximately 100 years ago, remains largely unchanged even today. In fact, the true face of the Western world, which brought culture, democracy, and freedom to Islamic countries, including Turkish geography, was entirely different.The struggle of Vazirov, who recognized this truth long ago and endeavored to expose the true nature of the West, is quite commendable.​